1995
DOI: 10.1095/biolreprod53.6.1271
|View full text |Cite
|
Sign up to set email alerts
|

Steroidogenic Activity, Insulin-Like Growth Factor-I Production, and Proliferation of Granulosa and Theca Cells Obtained from Dominant Preovulatory and Nonovulatory Follicles during the Bovine Estrous Cycle: Effects of Low-Density and High-Density Lipoproteins1

Abstract: The role of high- and low-density lipoproteins (HDL and LDL) in regulating steroidogenic activity, cellular viability and proliferation, and insulin-like growth factor-I (IGF-I) production was examined in granulosa and theca cells from dominant preovulatory (DO) and nonovulatory (DNO) bovine follicles. Follicles were obtained from pluriparous nonlactating beef cows at ovariectomy 24 h after administration of a luteolytic dose of prostaglandin F2 alpha (DO) or during the first follicular wave on Days 5-8 of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
19
1
2

Year Published

2000
2000
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(27 citation statements)
references
References 29 publications
(56 reference statements)
5
19
1
2
Order By: Relevance
“…A positive trend for HDL and LDL levels was also recorded in the follicular fluid of the cows fed CLA (P <0.1). Since in vitro studies have shown that both, HDL and LDL increase granulosa cells viability and the production of progesterone and IGF-I by the luteal cells (Bao et al, 1995;1997), results corroborate the hypothesis of a positive effect of dietary supplementation of CLA on reproduction. In agreement with a previous study (Castaneda-Gutierrez et al, 2007), plasma and follicular fluid IGF-I levels were higher in the CLA treated cows (P <0.05) (Figures 4 and 5).…”
Section: Resultssupporting
confidence: 69%
See 1 more Smart Citation
“…A positive trend for HDL and LDL levels was also recorded in the follicular fluid of the cows fed CLA (P <0.1). Since in vitro studies have shown that both, HDL and LDL increase granulosa cells viability and the production of progesterone and IGF-I by the luteal cells (Bao et al, 1995;1997), results corroborate the hypothesis of a positive effect of dietary supplementation of CLA on reproduction. In agreement with a previous study (Castaneda-Gutierrez et al, 2007), plasma and follicular fluid IGF-I levels were higher in the CLA treated cows (P <0.05) (Figures 4 and 5).…”
Section: Resultssupporting
confidence: 69%
“…Moreover, CLA increased the plasma lipoprotein concentrations in cattle (Trevisi et al, 2008). In vitro studies have demonstrated that high and low density lipoproteins (HDL and LDL) generally promote bovine granulosa cell viability (Bao et al, 1995) and stimulate greater progesterone and IGF-I secretions in bovine luteal cell cultures (Bao et al, 1997). The proposed anti-inflammatory effects of CLA may then protect the anti-oxidant paraoxonase1 (PON) from inactivation (Su et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, the detailed pattern of mRNA expression and production of IGF-I in bovine follicles remains controversial. Cattle granulosa cells were reported to produce IGF-I in vitro (Spicer et al, 1993;Bao et al, 1995;Chamberlain, 1998, 2000;Sirotkin et al, 1998), but one study concluded that IGF-I is not produced by these cells (Gutierrez et al, 1997). In the same way, IGF-I mRNA was detected in bovine granulosa cells (Spicer et al, 1993;Spicer and Echternkamp, 1995;Yuan et al, 1998;Schams et al, 1999), although other works report null or weak IGF-expression in only 17% of the follicles evaluated (Perks et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…3β-Hydroxysteroid dehydrogenase (3β-HSD) is an enzyme that catalyzes the synthesis of progesterone from pregnenolone (5). Thus, steroidogenic cells can be identified by the determination of 3β-HSD activity during the cell counting process (6). In goats, as in other mammals, the luteal cell size progressively increases as more and more small-sized cells achieve the process of cell differentiation to form large luteal cells during the progress of the luteal phase (2,3).…”
Section: Introductionmentioning
confidence: 99%